Identification of novel informative loci for DNA-based X-inactivation analysis - Musalkova, Dita; Minks, Jakub; Storkanova, Gabriela; Dvorakova, Lenka; Hrebicek, Martin (Blood cells, molecules & diseases, 2015)
The HUMARA assay, the most common method for evaluation of X-inactivation skewing in blood cells, has been reported to be usable in only about 80% of females, emphasizing the need for alternative methods for testing of HUMARA-uninformative individuals. We conducted an in silico search for potentially polymorphic tri-to-hexanucleotide repeats in the proximity of CpG islands located in 5' regions of X-chromosome genes to design five candidate assays (numbered I, II, III, IV, and V) combining methylation-specific restriction digest with PCR amplification in a manner similar to the HUMARA assay. The results obtained by these assays in 100 healthy females were compared to X-inactivation skewing measured by the AR-MSP method which is based on methylation-specific PCR amplification of the first exon of the AR gene. On the basis of statistical evidence, three of the novel assays (II, IV, and V), which were informative in 18%, 61%, and 55% of females in the cohort, respectively, may be used as alternatives or conjointly with the HUMARA assay to improve its reliability. The three new assays were combined with the HUMARA assay into a novel X-inactivation test leading to the increase of informative females in the cohort from 67% to 96%.
Keywords: Computer Simulation; Male; Androgen receptor; Polymerase Chain Reaction; polymerázová řetězová reakce; lidé středního věku; počítačová simulace; Biological Assay; Chromosomes, Human, X; studie případů a kontrol; metylace DNA; senzitivita a specificita; Exons; X-chromosome inactivation; mikrosatelitní repetice; modely genetické; DNA primery; CpG ostrůvky; Humans; Trinucleotide repeats; Middle Aged; CpG Islands; senioři; mužské pohlaví; Receptors, Androgen; Female; mladiství; DNA Primers; Aged; polymorfismus genetický; androgenní receptory; Case-Control Studies; ženské pohlaví; DNA methylation; Skewing; DNA Methylation; biotest; Polymorphism, Genetic; Adult; exony; inaktivace chromozomu X; Sensitivity and Specificity; X Chromosome Inactivation; Blood cells; Adolescent; dospělí; dítě; lidské chromozomy X; lidé; Models, Genetic; Child; Microsatellite Repeats